Ewolucja opowiadania od storytellingu do storysellingu i z powrotem. Paradoksy i wstępne rozpoznania terminologiczne - Płuciennik, Jarosław (Zagadnienia Rodzajów Literackich, 2024)
The article examines the evolution of the concept of “storytelling” in the context of the social history of media, showing how storytelling has changed from oral forms to contemporary digital forms and so called storyselling. The author undertakes a metatheoretical review of key concepts related to storytelling, examining both traditional narrative forms such as gossip and skaz, as well as modern concepts of “storyselling” and Olga Tokarczuk’s “tender narrator.” The paper focuses on the role of narrative in shaping political and media discourse, pointing to semantic changes that affect the contemporary way of understanding and presenting reality. The article emphasizes that storytelling is not only an integral element of culture, but also plays a key role in the processes of social communication, especially in the context of the convergence of media and digital narrative tools. In addition, the study explores how the rise of digital platforms has reshaped the dynamics of storytelling, allowing for new forms of interaction between creators and audiences. The author argues that the current media environment, through its fragmented and participatory nature, challenges traditional narrative structures, fostering more collaborative and decentralized forms of storytelling. Ultimately, the article suggests that understanding the evolution of storytelling is crucial for analyzing contemporary cultural phenomena and their impact on public discourse.